1994
DOI: 10.1093/oxfordjournals.eurheartj.a060420
|View full text |Cite
|
Sign up to set email alerts
|

The significance of anticardiolipin antibodies and anti-heart muscle antibodies for the diagnosis of postpericardiotomy syndrome

Abstract: Postpericardiotomy syndrome (PPS) is a frequent complication after cardiac surgery. In a recent study, elevated anticardiolipin antibody (ACLA) titres were observed in patients with PPS. The value of anti-heart muscle antibodies (AHA) for the diagnosis of PPS remains controversial. Therefore, a prospective double-blind study was performed to test the sensitivity and specificity of ACLA and AHA for the diagnosis of PPS. ACLA titres (ELISA) and AHA, elevated by immunofluorescence, the clinical course and routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
0
17
1
1
Order By: Relevance
“…6 The latency from pericardial injury to the clinical onset of symptoms and the usually good response to antiinflammatory therapy support this hypothesis. 6,7 Delayed manifestation of pericarditis occurs after open cardiac surgery and also after chest trauma. 6-8 Nomura et al 8 showed that there is no correlation between the extent of injury caused by a heart operation and PS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The latency from pericardial injury to the clinical onset of symptoms and the usually good response to antiinflammatory therapy support this hypothesis. 6,7 Delayed manifestation of pericarditis occurs after open cardiac surgery and also after chest trauma. 6-8 Nomura et al 8 showed that there is no correlation between the extent of injury caused by a heart operation and PS.…”
Section: Discussionmentioning
confidence: 99%
“…9 The significance of antiheart muscle antibodies (AHA) in the diagnosis of PS remains controversial because even severe PS without occurrence of AHA has been described. 7 Because of similar clinical symptoms, relevant differential diagnoses of PS include pneumonia, pleuritis after chest tube placement, atelectasis, viral or bacterial endocarditis, and deep wound infection. 10 As reported recently, 3 PS did not occur when the Lorenz introducer was used.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of a variety of both heart-and non-organ-specific antibody levels prior to and following cardiac surgery were detected [5]. It has been shown that anti-sarcolemma antibodies to both heart and skeletal muscle, antiendothelial antibodies, anti-smooth muscle antibodies, and anti-nuclear antibodies (ANA) appeared more often in patients with PPIS.…”
Section: Specific Antibodies Versus Systemic Unspecific Autoimmune Rementioning
confidence: 99%
“…Therefore, the pathogenesis of this syndrome may involve endocardial surface injury. In addition, small contained perforations could cause an immune response and sterile inflammation in both the pericardium and the pleural space [2,14]. Hence, subacute perforation causing epicardial injury may also play a significant role in the development of this syndrome.…”
Section: Resultsmentioning
confidence: 99%